Human infection with pandemic Influenza (H1N1): A Review Article - Karmacharya, Ranjita (Janapriya Journal of Interdisciplinary Studies, 2019)
Swine flu, also known as the H1N1 virus, is new strain of an influenza virus that causes symptoms similar to the regular flu. It originated in pigs, but is spread rapidly from person to person. Therefore, the objectives of this article are to highlight on H1N1 Influenza, its mode of transmission, risk factor, clinical spectrums and preventive ways. Studies published relevant to swine flu was searched through scientific databases like MEDLINE, Pubmed and online search engines like ‘Google Scholar’. Eligible studies involved at least one factor related to ‘influenza A virus’, ‘H1N1 subtype’, ‘epidemiology’, ‘transmission” and ‘preventive measures’ etc. Searches were limited to human only and also looked at the websites of the leading health authorities (e.g. WHO, CDC, HPA). Swine is a new flu virus that appears in human and spreads very quickly from person to person. In Nepal, the first case was detected on June 2009 after that the case is increasing day by day. In 2010 till May there were 172 confirmed positive cases, likewise on August 7, 2017 there were 10 death and 354 positive cases of swine flu in Nepal. Therefore, Government of Nepal has broadcasted awareness programs, organized seminars and meetings, to make people aware regarding H1N1 Influenza. But, it seems challenging to decrease its outbreak in Nepal because of low financial resources, low manpower, limited technology and political instability.